#TITLE_ALTERNATIVE# - (NIM : 10211023), PRADIPTO
The most common collision model of LBM is the BGK with a constant single relaxation time Ƭ. However, BGK suffers from numerical instabilities. These instabilities could be eliminated by implementing LBM with multiple relaxation time. Both of those scheme have implemented for incompressible 2 dimensions lid-driven cavity.The stability analysis has done by finding the maximum Reynolds number and velocity for converged simulations. The accuracy analysis is done by comparing the velocity profile with the benchmark results from Ghia, et al and calculating the net velocity flux. The tests concluded that LBM with MRT are more stable than BGK, and have a similar accuracy with grids equal to (128 x 128). The maximum Reynolds number that converges for BGK is 3200 and 7500 for MRT respectively.